2013
DOI: 10.11646/zootaxa.3608.5.7
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Pseudopaludicola Miranda-Ribeiro (Leiuperinae: Leptodactylidae: Anura) from the Cerrado of southeastern Brazil

Abstract: A new species of Pseudopaludicola is described from the Cerrado of southeastern Brazil. Pseudopaludicola facureae sp. nov. is diagnosed from the P. pusilla species group by the absence of either T-shaped terminal phalanges or toe tips expanded, and distinguished from almost all recognized taxa currently assigned to Pseudopaludicola (except P. canga, P. giarettai, and P. hyleaustralis) by possessing a non-pulsed advertisement call. However, the advertisement call of the new species consists of the emission of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…In addition, P. canga and P. facureae can be distinguished from almost all congeners (except for P. giarettai and P. hyleaustralis) based on their non-pulsed advertisement calls (Andrade & Carvalho 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, P. canga and P. facureae can be distinguished from almost all congeners (except for P. giarettai and P. hyleaustralis) based on their non-pulsed advertisement calls (Andrade & Carvalho 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The frog genus Pseudopaludicola Miranda‐Ribeiro ; is widespread in lowland South America and is considered a monophyletic taxon due to the presence of a hypertrophied antebrachial tubercle in its members (Lynch ). This genus, allocated to the subfamily Leiuperinae (Pyron & Wiens ), comprises 17 valid species (Andrade & Carvalho ; Cardozo & Toledo ; Roberto et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the cryptic pattern (Pansonato et al 2012;Carvalho et al 2015aCarvalho et al , 2015b, sympatric occurrence is commonly observed among species of the genus Pseudopaludicola (Giaretta & Facure 2009;Loebmann & Haddad 2010;Magalhães et al 2014;Andrade et al 2016). This indicates that the species differ minimally in how they use natural resources and breeding sites, and the advertisement call is one of the main prezygotic barriers to reproductive isolation between them (Loebmann & Haddad 2010;Pansonato et al 2012;Andrade & Carvalho 2013;Magalhães et al 2014;Carvalho et al 2015aCarvalho et al , 2015b. in syntopy at dusk (around 18:00-18:30 h) in a flooded field covered by emergent vegetation near the banks of the Itapecuru River.…”
mentioning
confidence: 99%
“…The small toad-like frogs of the Neotropical genus Pseudopaludicola comprise seventeen species that are distributed along the eastern slopes of the Andes from northern Colombia to Argentina (Andrade and Carvalho, 2013;Frost, 2013). Lynch (1989) recognized a monophyletic group of Pseudopaludicola pusilla based on the presence of T-shaped terminal phalanges.…”
mentioning
confidence: 99%